Self Esteem and Career Adaptability Among College Graduates: The Role of Career Decision Self Efficacy as Mediating Variable - Sitorus, Veronica; Erlin, Nia Ariyani (Journal of Management and Administration Provision, 2025)
The increasing challenges in the career world ultimately require human resources who are able to adapt quickly to changes and developments. The purpose of this study is to explain how self-esteem affects adaptability in careers by using self-efficacy in career decision-making as a mediator. This quantitative study involved 200 respondents selected using a purposive sampling approach, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) 4.0. The results of the study indicate that career adaptability and self-efficacy in career decision-making are positively and significantly influenced by self-esteem. The relationship between self-esteem and career adaptability is mediated by self-efficacy in career decision-making, which also has a positive and significant impact on career adaptability. Career Construction Theory (CCT) in this study states that fulfilling basic psychological needs such as self-esteem can increase career decision self efficacy, which ultimately enhances career adaptability. The findings of this study highlight the importance for university graduates to develop self-esteem as a means to enhance confidence in career decision-making and career adaptability, especially in facing the challenges of an increasingly competitive career world.